Chaotic Image Encryption using Two Level Scrambling - SUBHASHINI, K.; AMUTHA, R.; MOHAMMED HASHIM, B. A. (Advances in Electrical and Computer Engineering, 2025)
With the introduction of the 5G technology, transmission of multimedia data is very high which demands data security. Image encryption techniques secure the transmission of image data from the intruder. We proposed a one-dimensional chaotic map whose chaotic behaviour over a wide range of control parameters is verified experimentally. Image encryption algorithm using two level permutations and one level diffusion is proposed in this paper. First level permutation is done on block level using one chaotic sequence. In the second level, entire image is permuted. Row and column diffusion is done using two chaotic sequences. From the experimental results and analysis, it is evident that the proposed image encryption algorithm resists differential and statistical attacks. Index Terms--chaos, encryption, image, information theory, multimedia systems.